Hysterectomy: Indications and depression as adverse psychological consequence - Syed, Tehmina Parveen; Devi, Rekha; Kumar, Rakesh; Devi , Ramna (Journal of Pakistan Psychiatric Society, 2021)
Abstract:Hysterectomy is not a life threatening procedure but Women who undergo hysterectomy face a multitude of physical and psychosocial problems, estrogen deficiency (in case of removal of ovaries) may have more detrimental effect on women’s health. Feeling of loss of femminity is also a main cause of anxiety and depression after hysterectomy.Studies showed that patient education about potential outcomes after hysterectomy may enhance their satisfaction with the procedure and also less or no long-term psychological morbidities, 10, 11 but still the association between hysterectomy and subsequent, long-term psychological health is not well defined. The present study explores the common indications of hysterectomy and its subsequent long-term psychological effects.OBJECTIVE:To demonstrate common indications of hysterectomy in our hospital.To assess long-term psychological impact of hysterectomy. Materials and methods:We conducted prospective observational study from Jan 2018 to July 2020. Total 112 hysterectomies were performed during this period. We observed common indications of hysterectomies and assessed long-term psychological effects by using DSM-V and Beck Depression Inventory questionnaire.Results:In Peri-menopausal women, the most common indication of hysterectomy was heavy menstrual bleeding and majority were due to uterine fibroids, while, in post-menopausal women the main reason was post-menopausal bleeding.Our study revealed that women who experienced premature menopause had developed severe depression after their hysterectomy, hence they require more support and counselling to maintain good psychological health.